2007
DOI: 10.1183/09031936.00007306
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological and pharmacological interventions to prevent or reduce airway remodelling

Abstract: In the present review of airway remodelling and its response to therapies, clinical observations about airway physiological abnormalities, assumed to be caused by remodelling processes, are related to what is known about the components of structural changes from airway sampling and histopathological analysis. The review focuses on three important diseases: asthma, chronic obstructive pulmonary disease and bronchiolitis obliterans syndrome (BOS), which occurs commonly after lung transplantation as a manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 126 publications
(148 reference statements)
0
21
0
1
Order By: Relevance
“…Recent reviews suggest that evidence that any current treatment can prevent or reduce airway remodelling is conflicting at best [9,40], and there is an urgent need for research in this area. A better understanding of the root cause of inflammation should lead to the development of both curative treatments and effective prevention strategies.…”
Section: Inflammation: a Key Pathology In Asthmamentioning
confidence: 99%
“…Recent reviews suggest that evidence that any current treatment can prevent or reduce airway remodelling is conflicting at best [9,40], and there is an urgent need for research in this area. A better understanding of the root cause of inflammation should lead to the development of both curative treatments and effective prevention strategies.…”
Section: Inflammation: a Key Pathology In Asthmamentioning
confidence: 99%
“…Lifestyle changes, such as smoking cessation, prevention of infections or modulating immune responses, as well as reduction of exposure to potential environmental hazards, such as allergens and pollutants, both at home or at the workplace, may help to reduce airway remodelling but are often difficult to achieve [6,34,35]. Animal models showed that early interventions, such as with inhaled corticosteroids or leukotriene receptor antagonists, may prevent many aspects of airway remodelling, at least partly [3,7,8].…”
Section: Tablementioning
confidence: 99%
“…There is evidence both from animal models and human clinical trials that environmental or pharmacological interventions may reduce various aspects of airway remodelling [6,34,35].…”
Section: Is Airway Remodelling Reversible and To What Extent?mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from modulating the bronchoactive and proinflammatory effects of CysLTs, LTRA may also protect against several aspects of CysLT-induced airway hyperresponsiveness and airway remodeling [66,67], as CysLT 1 Rs have been found on the airway smooth muscle in both central and peripheral airways [25]. In line with these findings, in a study by Riccioni and colleagues, 12 weeks of treatment with montelukast (10 mg once daily) both as monotherapy and in combination with inhaled corticosteroids (budesonide 400 µg twice daily) decreased airway hyperresponsiveness in patients with mild-to-moderate persistent asthma [68].…”
Section: Montelukast In the Treatment Of Asthma And Beyondmentioning
confidence: 99%